2019
DOI: 10.1002/pmrj.12160
|View full text |Cite
|
Sign up to set email alerts
|

Using Clinical Balance Tests to Assess Fall Risk among Established Unilateral Lower Limb Prosthesis Users: Cutoff Scores and Associated Validity Indices

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(63 citation statements)
references
References 73 publications
(218 reference statements)
3
57
1
1
Order By: Relevance
“…For example, falls from intrinsic destabilizing forces were associated with lower average FMW test (0.74 m/s) and higher TUG test outcomes (25.6 seconds). Existing research has established thresholds for identifying patients with LLA at risk for multiple falls (TUG test thresholds ranging from 9.25 to 19 seconds) 9,27 . The results from this study suggest a potential relationship between poor functional outcomes after dysvascular LLA and fall types.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…For example, falls from intrinsic destabilizing forces were associated with lower average FMW test (0.74 m/s) and higher TUG test outcomes (25.6 seconds). Existing research has established thresholds for identifying patients with LLA at risk for multiple falls (TUG test thresholds ranging from 9.25 to 19 seconds) 9,27 . The results from this study suggest a potential relationship between poor functional outcomes after dysvascular LLA and fall types.…”
Section: Discussionmentioning
confidence: 69%
“…The TUG test 37,38 is an assessment of basic mobility, and is measured as the time (in seconds) required for the participant to rise from a chair, walk 3 meters, return to the chair, and sit back down as quickly and safely as possible, using a handheld stopwatch and a 46‐cm seat 43 . The TUG has established cut‐off scores to indicate fall risk for people with LLA 9,27 . Each participant was provided one practice trial, and the average of two subsequent trials was reported.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations